OsAUX1 controls lateral root initiation in rice (Oryza sativa L.). (7th January 2015) - Zhao, Heming; Ma, Tengfei; Wang, Xin; Deng, Yingtian; Ma, Haoli; Zhang, Rongsheng; Zhao, Jie
Abstract: Polar auxin transport, mediated by influx and efflux transporters, controls many aspects of plant growth and development. The auxin influx carriers in A rabidopsis have been shown to control lateral root development and gravitropism, but little is known about these proteins in rice. This paper reports on the functional characterization of OsAUX 1 . Three OsAUX 1  T‐DNA insertion mutants and RNAi knockdown transgenic plants reduced lateral root initiation compared with wild‐type (WT) plants. OsAUX 1 overexpression plants exhibited increased lateral root initiation and OsAUX 1 was highly expressed in lateral roots and lateral root primordia. Similarly, the auxin reporter, DR5‐GUS, was expressed at lower levels in osaux 1 than in the WT plants, which indicated that the auxin levels in the mutant roots had decreased. Exogenous 1‐naphthylacetic acid (NAA) treatment rescued the defective phenotype in osaux 1‐1 plants, whereas indole‐3‐acetic acid (IAA) and 2, 4‐D could not, which suggested that OsAUX 1 was a putative auxin influx carrier. The transcript levels of several auxin signalling genes and cell cycle genes significantly declined in osaux 1, hinting that the regulatory role of OsAUX 1 may be mediated by auxin signalling and cell cycle genes. Overall, our results indicated that OsAUX 1 was involved in polar auxin transport and functioned to control auxin‐mediated lateral root initiation in rice. Abstract : In this study, we detail investigated function of OsAUX 1 (LOC_Os01g63770). OsAUX 1 was abundantly expressed in root tips, lateral roots and lateral root primordial, three OsAUX 1  T‐DNA mutants and RNAi plants exhibited a reduced number of primordia and lateral roots, and the overexpression lines exhibited an increased number of primordia and lateral roots. Analysis of IAA content detection and DR5::GUS expression suggested that there was significant reduction in auxin levels in the root tips of osaux1 mutants, and transcriptome analysis also showed that expressions of several auxin regulated genes were altered in osaux1 . The results indicated that OsAUX 1 was involved in polar auxin transport and controlled lateral root initiation in rice.